Synthesis and recognition properties of colorimetric anion chemosensor bearing 2,4-dinitrophenylhydrazone and indene-1,3-dione moieties - Aydın, Fatma (European Journal of Chemistry, 2014)
A new receptor named, 2-(2-(2,4-dinitrophenyl)hydrazono)2H-indene-1,3-dione, used as a colorimetric sensor based on 2,4-dinitrophenylhydrazone derivative of ninhydrin was synthesized by simple step with good yields and characterized by IR and 1H, 13C NMR and MS spectroscopic techniques. The anion recognition properties were studied by UV-Vis spectroscopic technique. The results showed that the receptor had a higher affinity to F-, CN-, H2PO4-, CH3COO- and OH-, but showed no evident binding with Cl-, Br- and I-. Binding of the reseptor to anions such as CN-, AcO-, F-, H2PO4- and OH-exhibited an obvious color change from greenish yellow to purplish blue, which was possible to observe by the naked eye.